The missing gene : psychiatry, heredity, and the fruitless search for genes - Joseph, Jay (Algora Pub., 2006)
Genetic research in psychiatry has reached the crisis stage due to the continuing failure to identify the genes presumed to cause many of today's most troubling mental disorders. Dr. Joseph presents a clearly argued explanation for this failure, and warns that by focusing on the wrong goal, precious resources are diverted from the search for real causes and treatments. We were supposed to have discovered the genes that cause mental disorders by now; but we have not. Unfortunately, researchers and reviewers almost never consider the possibility that genes for the major psychiatric conditions have not been identified for one insuperable reason: they do not exist. At bottom, the search for genes in psychiatry is based on the uncritical acceptance of the results of family, twin and adoption studies. Professionals, students and the public must be informed that these studies do not provide scientifically acceptable evidence in support of genetics. What causes psychological distress? Are we shaped primarily by our environment or by our genes? These very old questions remain controversial. Quantitative genetic tests such as family, twin and adoption studies have laid the foundations for the current worldwide effort to identify the genes presumed to underlie psychiatric disorders such as schizophrenia, bipolar disorder, A.D.H.D., autism and so on. This book argues that molecular genetic researchers take a hard second look at these foundations, which are far weaker than they believe. This book is urgently needed. The results of genetic research have a profound effect on both scientific and public thinking, as well as on social policy decisions. This book presents an alternative view to the one that currently dominates psychiatry and psychology. The author calls for a paradigm shift in psychiatry away from genetic explanations of mental disorders, and towards a greater understanding of how family, social and political environments contribute to human psychological distress. This book is destined to play an important role in this shift. Like The Gene Illusion, it will be a controversial book and is sure to spark intense discussion.